HUBUNGAN PENTINGNYA PENGGUNAAN KELAMBU DENGAN TERJADINYA PENYAKIT MALARIA DI DESA LUMOLI KABUPATEN SERAM BAGIAN BARAT - Lihi, Maryam; Tunny, Ira Sandi; Sillehu, Sahrir (PT.Mantaya Idea Batara, 2024)
Malaria is one of Indonesia's public health problems. It is crucial to conduct research on alternative malaria prevention methods. Using mosquito nets while sleeping is one way to reduce mosquito bites. This study aims to determine whether the prevalence of malaria in Lumoli Village, West Seram Regency, is influenced by the use of mosquito nets. This study's design was cross-sectional. The study focused on the three hundred houses that comprise Lumoli Village as a whole. There was no significant correlation between malaria and the use of mosquito nets, based on the results of statistical tests at p > 0.05 and p = 1,000. The incidence of malaria in Lumoli Village, West Seram Regency, was statistically unrelated to the use of mosquito nets.